Assess the knowledge on lactational amenorrhea as a contraceptive method among mothers of infants aged 0-6 months receiving MCH services in a selected urban health centre at Chennai. - MRS. T. MAHALAKSHMI M.SC (N) (International Journal of Pharma and Bio Sciences, 2017)
Lactation is a natural defense against pregnancy. As long as a mother is nursing, she is delaying the return of fertility. The natural mechanism triggered by breastfeeding interrupts ovulation and the menstrual cycle. The World Health Organization (WHO) recommends starting breastfeeding as soon as possible following delivery. Even though breastfeeding is a natural event, most mothers feel the need of reliable counseling and family and support. The main aim of the study is to assess the knowledge on lactational amenorrhea as a contraceptive method among mothers of infants aged 0-6 months receiving MCH Services in a selected urban health centre at Chennai. Descriptive research design was adapted for this study. Sample Size :50 Mothers of infants aged 0-6 months who are all meet the inclusion criteria is a sample were selected by using Convenient sampling technique. The study results revealed that regarding knowledge on lactational amenorrhea as a contraceptive method among mothers of infants aged 0-6 months 25(50%) had inadequate knowledge, were as 12(24%) had moderately adequate knowledge, 13 (26%) had adequate knowledge The present study concludes that the mothers have a poor knowledge toward Lactational amenorrhea method as a Contraceptive method. Our findings also showed that the level of knowledge on exclusive breast feeding was low among Indian mothers. Thus, it is important to provide education to mothers on benefits of LAM as a natural contraception.